Epistemology of Governmental Science: A Paradigmatic Study of Thomas Kuhn's Scientific Revolution - Abd. Rasyid, Syamsul Bahri; Robo, Sahrail; Suswanta (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This paper aims to describe cross-disciplinary approaches in the science of government, paradigms, schools of thought, and their relationship with Thomas Kuhn's scientific revolution, all of which are analyzed epistemologically-paradigmatically. The research method used is qualitative-library study, which relies on literature in books and scientific journals, then described descriptively. This paper explains that government science seeks to give birth to new paradigms (Kybernology and Islam), new schools of thought (Governance and Timoho), new branches (government intelligence), as well as to strengthen approaches (critical approaches of the Frankfurt School) and new research (research participatory). These efforts are then an attempt by government science to break away from the intervention of political science and administrative science, as stated in the objectives of the Indonesian Government Science Study Program Unit (KAPSIPI) when viewed from the perspective of Thomas Kuhn's scientific revolution. This paper contributes to the epistemological-paradigmatic study of government science. Ontological and axiological studies need to be carried out using approaches that are still rarely used by government science activists.